Development of the methodological approach to the selection of technologies for environmentallysafe water drainage in populated areas - Teliura, Nataliya (Eastern-European Journal of Enterprise Technologies, 2018)
The methodological approach to the selection of a technological measure of environmentally safe water drainage in populated area located on the eutrophied water sites was developed. The use of this approach makes it possible to involve professionals of various fields from local authorities in the management of ecological safety of populated areas from the positions of their sustainable development. The essence of the methodological approach implies using the analytic hierarchy process (AHP). The criteria stated as constituents of sustainable development – environmental, social, and economictechnological – were proposed and used for it. Appropriate specialists as experts relied on the information of various types (statistics, prediction, and direct measurement data) on a particular populated area, give their own judgments regarding priority advantages of criterial features. The results of processing the judgment of experts in accordance with a formal AHP procedure form the basis for decision making when selecting technological measures of environmentally safe water drainage in a particular populated area. The multicriterial hierarchical structure of the selection of technological measures is represented by a sequence of actions comprising three stages: construction of a hierarchical model for comparison of criterial features; formation of matrices of pairwise comparisons of the elements of each hierarchy level and determining their weight coefficients; determining global weight coefficients, consistency index and selection of the best option. The advantage of the proposed multicriterial methodological approach is the possibility to unite into a single decisionmaking algorithm the source data that differ in both their content (environmental, social, and economictechnological) and in their form of representation (statistical, predicting, direct measurement data, expert estimations). Testing the developed methodological approach was carried out using the example of a typical populated area, located at the eutrophied water site – the source of drinking water supply and of recreational use. The obtained results, despite a fairly large dimensionality of the hierarchy members array, revealed the achievement of a suitable consistency level, which demonstrates their reliability. The developed methodological approach can be used to substantiate the improvement or construction of a new drainage system of a populated area, located on the eutrophied water site